Exploring the utilisation and effectiveness of implementation science strategies by cystic fibrosis registries for healthcare improvement: a systematic review - Rob G. Stirling; Bhumika Sood; Macken J.L. Stirling; Tom Kotsimbos; Dominic T. Keating; Catherine E. Rang; James M. Trauer; Alan C. Young; Christiaan Yu; Julianna Bailey; Peter Wark; Angela Melder; et al. (European Respiratory Review, 2025)
Background Cystic fibrosis (CF) registries capture important information in high-burden health domains to support improvement in health outcomes, although a number of unanswered questions persist, as follows. 1) Do CF registries utilise implementation science strategies to improve patient outcomes? 2) Which implementation strategies have been engaged? 3) Has the engagement of these strategies been effective in improving clinical outcomes? Methods We undertook a systematic review to exploring the use of implementation science strategies by CF registries for healthcare improvement. We searched MEDLINE, Embase, Scopus, Emcare and Web of Science databases for use of Expert Recommendations for Implementing Change (ERIC) implementations and use of the Knowledge to Action framework for improvement. We used the Risk of Bias in Non-randomised Studies – of Interventions tool for risk-of-bias assessment. Results 1974 citations were identified and 12 studies included. Included studies described 45 ERIC implementation strategies from nine categories. Strategies included “use evaluative and iterative strategies” (n=9) and “develop stakeholder interrelationships” (n=10). Least-used strategies were “utilise financial strategies” (n=1), “support clinicians” category (n=3) and “provide interactive assistance” (n=2). All 12 studies utilised monitoring of knowledge use, and assessing barriers and facilitators of knowledge use. Only seven studies utilised mechanisms to sustain knowledge use. Discussion Reported studies describe significant benefits in important CF outcomes for people with CF reported at site-specific and population levels. Studies highlighted the importance of governance, leadership, patient and family engagement, multidisciplinary engagement, quality improvement, data and analytics and research. The ready availability of clinical performance data feedback to clinicians and patients by CF registries is likely to strengthen the effectiveness of CF registries in driving healthcare improvement within a learning health system.